Pengaruh Komunikasi Internal Terhadap Produktivitas Kerja Karyawan Bidang Tata Graha Pada Hotel Berbintang Di Kecamatan Ajibata Kabupaten Toba Samosir - Muhammad Hamdani (Jurnal Ilmiah Akomodasi Agung, 2019)
This study aims to analyze internal communication and work productivity of employees in star-rated hotels in Ajibata District, Toba Samosir Regency. To find out whether internal communication has a significant effect on employee productivity in the field of housekeeping. In this study quantitative types of research are used. The research data was collected from 15 respondents, the respondents' answers were then processed using the SPSS program by conducting validity tests, reliability tests, and simple linear regression tests. The results of the analysis show that internal communication has an effect of only 3.6% on work productivity. Viewed from these results, it can be said that internal communication has little effect on work productivity